The Effect of Using Letter Card Media on Qur'an Learning on The Ability TO Read Hijaiyah Letters in Early Childhood - Syarifah Syarifah; Ellisa Fitri Tanjung (STAI Serdang Lubuk Pakam, 2023)
One of the learning achievements is influenced by the use of media, errors in media selection actually have an impact on non-achievement. With regard to that, the purpose of this study is to determine the effect of letter card media on the ability to read hijaiyah letters of Early Childhood RA Dinul Hasanah Stabat. This research uses a quantitative approach, with an experimental method. Data collection methods using observation and performance tests. To test the research hypothesis using the T-test formula. The results of this study indicate that the analysis of the two classes of pretests and posttests for the control class with a mean of 84.28 and the experimental class of 66.25, with a median of the control class of 4.5 and the experimental class of 8. The media is very influential on the ability to read hijaiyah letters indicated by the homogeneity test obtained a tcount value of 3.84 while after the T-test is carried out, a ttable of 2.6 is obtained, this shows at the 5% significance level and the results show that the tcount value is 3.84> ttable value of 2.6 . So, there is an influence of letter card media on the ability to read hijaiyah letters in early childhood Raudhtul Athfal (RA) Dinul Hasanah Stabat. This research has implications for improving learning, especially the introduction of hijaiyah letters.